Cystolitholapaxy and laparoscopic sacrocolpopexy in a case of multiple urinary bladder calculi & vault prolapse. (December 2019) - Hiremath, Akkamahadevi C; K.S., Shivakumar
Abstract: Vesical calculi are more common in men than women. The prevalence in women is less than 2%. Multiple vesical calculi in chronic cases of utero vaginal prolapse or vault prolapse is rare. Urinary stasis, urethral kinking along with chronic infection are the probable predisposing factors for stone formation [2 ]. We report a case of 65 year old female, with mass per vagina since 10 years, who developed acute urinary retention due to impaction of vesical calculus at the external urethra meatus. Subsequently in a span of 12 h she passed 3 more vesical calculi. KUB X-ray failed to show any calculi but Computed Tomography(CT) Kidney Ureter Bladder (KUB) showed 2 vesical calculi. After cystolitholapaxy she underwent laparoscopic sacrocolpopexy for vault prolapse. In cases of chronic uterovaginal prolapse or vault prolapse X-Ray KUB should not miss the prolapsed part of the cystocele as calculi are present in the most redundant part. Chances of missing radiolucent uric acid calculi is high. In such cases CT KUB is essential.